Augmented Reality (AR)-Based E-Module to Improve High School Students' Understanding of Fluid Concepts and Critical Thinking Skills - Soraya, Sofiyan; Purwanti, Endah; Efelina, Vita; Wibowo, Firmanul Catur; Sugihartono, Iwan (WaPFi (Wahana Pendidikan Fisika), 2025)
The development of digital technology has brought significant changes in the world of education, including in the development of innovative and interactive learning media. One of the challenges in learning physics at the high school level is students' low understanding of complex fluid concepts, especially in Bernoulli's Law and Torricelli's Theorem. This study aims to develop an e-module based on Augmented Reality (AR) technology equipped with LKPD, and analyze its effectiveness in improving students' critical thinking skills. The research method used is Research and Development (RD) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The developed e-module presents fluid material content visually and interactively through AR simulations, and integrates elements of science, technology, engineering, and mathematics in the context of physics learning. Implementation was carried out in high schools, with data collection through pre-tests, post-tests, and student and teacher response questionnaires. The results showed that the AR-based e-module equipped with LKPD was suitable for use based on validation by media experts (89%) and material experts (82%), and obtained an increase in critical thinking skills of 0.62 (moderate category) based on the gain test. In conclusion, the development of an AR-integrated e-learning module on the Bernoulli and Torricelli concepts can be an effective innovation to improve students' conceptual understanding and critical thinking skills in physics learning in the digital era.